Environmental taxes shadowing: theoretical aspect - I.V. Tiutiunyk; I.A. Tenytska; P.M. Vostrykov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The ecological disasters caused by deforestation, exploitation of seas and soils, pollution of atmospheric air and water, that are the consequences of an excessive anthropogenic impact on the environment. These and other issues of preservation of biodiversity and the ecosystem in general are on the agenda of international organizations and countries’ governments. To compensate for the damage caused to the environment, each country introduced environmental taxes and fees. However, as practice shows, such taxes do not fulfill the functions assigned to them. One of the reasons for the environmental collapses inherent in Ukraine is that there are such mechanisms that allow avoiding (evading) the payment of mandatory environmental payments. In addition to the fact that the size of the environmental payments is not commensurate with the amount of damage caused, the accumulated funds are not used for their intended purpose. Taking this into account, the domestic economy faced the problem of environmental tax shadowing. The primary reason for this is that the amount of environmental tax directly affects the company's profit, and therefore, the business entity may violate environmental legislation for reducing expenses and increasing income, especially when the sanctions for such offenses are not significant. The article confirmed the relevance of the issue of de-shadowing of the environmental tax in Ukraine (by the Publish or Perish instrument focusing on relevant works indexed by the Scopus database), however earlier this issue was reflected in scientific works partially. The normative and legal principles of environmental control were studied, since this tool is intended for the de-shadowing of environmental taxes and fees, as well as for control over the legality of actions performed by state authorities. The successful consequences and shortcomings of the reform of environmental control, which thoroughly began in 2014, were also assessed. Current domestic system of environmental control is not perfect, because of the cases of exceeding the powers of officials in granting permits or concealing environmental crimes. These consequences are the first signs of failure to implement horizontal reforms. The study of sectoral reforms of state environmental control implementation demonstrates that they also have their shortcomings, and this is reflected in the state of the natural environment. Therefore, the analysis confirmed the need for further research on the environmental tax de-shadowing, in order to increase the effectiveness of environmental losses countermeasures.